Item response theory in the development of a scale to measure harassment against women in online games - Pequeno de Mello, Agatha; Anjos, Adilson dos; Giolo, Suely R.; Zanin, Fernanda da Conceição (Brazilian Journal of Biometrics, 2023)
This study aimed to develop a scale to measure the harassment experienced by women in multiplayer online games. The study sample consisted of 324 Brazilian female players aged 18 to 44 years recruited from an online survey. Item Response Theory (IRT), particularly the graded response model, was used to evaluate the performance of the items proposed to measure the cited harassment. Moreover, linear regression was used to investigate the association between some women’s characteristics and the scale. The results showed that the proposed scale is a nine-item unidimensional psychometric instrument suitable for measuring and better understanding the harassment experienced by women in online gaming spaces. In addition, the association analysis evidenced a high level of harassment among women who reported playing using female nicknames and playing more than three types of games. Finally, most of those who reported a preference for playing with female players had already experienced a high level of harassment.